Tourism content on Twitter (X) during a crisis - Luis Alfonso Garay Tamajón; Maartje Roelofsen (Annals of Tourism Research Empirical Insights, 2024)
This study explores the themes and actors that dominated tourism-related tweets over the first two years of the COVID-19 emergency (2020-2021) and examines Twitter (X)'s potential as a communication tool within tourism crisis management. A mixed-methods research design was adopted to analyse almost half a million Twitter (X) posts that included the keyword 'tourism' and pandemic-related terms. The outcomes suggest that a select number of actors and user categories generated most of this Twitter (X) content and many of these had no specific involvement in tourism or displayed bot-like patterns of interaction. Content relating to crisis management abounded but so did content about geek culture, cryptocurrency, and NFTs. This calls for further monitoring and moderation of content and profiles on social media platforms.
Keywords: 330; COVID-19 pandemic; Crisis management; Misinformation; Social media; Tourism; Twitter (X)